Tbe aleph partial derivative - Hayek, N.; González, J.; Falcón, S. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In this paper we define the ";aleph"; partial derivative through an adequate generalization of the usual concept of. finite increment. The main properties of this operator are also established. This derivative extends the classical partial derivative in the same way that the ";aleph"; derivative (Aldanondo [1]) generalizes the familiar derivative of an arbitrary function.